Determination of Various Flocculants' Performance in Flocculation of Lignite Waste Pulps - Cebeci, Y.; Sarioglu, M.; Kahriman, A. (Asian Journal of Chemistry, 2010)
In this study, the performance of the different flocculants, in the flocculation of the pulps prepared using lignite samples, has been investigated taking into consideration floc settling rate, supernatant turbidity and filtration. In the experiments, their anionic, cationic, non-ionic flocculants and mixtures have been used. For the high settling rate and low turbidity the best results have been obtained with non-ionic flocculants. Regarding the filtration anionic flocculant has given the best result.